Navigational Surgery of the Facial Skeleton [electronic resource]: - 435064 Schramm, Alexander; Gellrich, Nils-Claudius; Schmelzeisen, Rainer; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
42